Effect of agronomic factors on coenoses of natural pasture communities in Apulia environments - Martiniello P.; Nardelli F. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Herbage grasses of native pastures in the region Apulia are quite variable in biomass production and floristic composition. Experiments were planned for improving productivity using chemical fertilisers in four locations for studying the effect of mineral applications on biomass, composition of flora, nutritive values and chemical components of topsoil. The fertilisers used (60 kg ha-1 of nitrogen, 80 kg ha-1 of phosphorus and phosphorus plus nitrogen at a rate of 70-32 kg ha-1) were compared to unfertilized control plots. All fertiliser applications positively influenced dry matter production, the flora composition of sward and slowly affected the chemical components of the topsoil. Nitrogen and phosphorus applications promote competition and selection among flora, favouring the development of species of grasses and legumes. Phosphorus plus nitrogen fertiliser increases the agronomic fertility of soil, favouring development of plants with a smaller degree of change in the flora composition in comparison to the unfertilised control.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)